2021
DOI: 10.1080/26395916.2021.1931452
|View full text |Cite
|
Sign up to set email alerts
|

Towards a caring transdisciplinary research practice: navigating science, society and self

Abstract: Transdisciplinary research that bridges science and society is needed to address the complex social-ecological sustainability challenges we are facing. However, many transdisciplinary researchers grapple with balancing the competing demands of scientific rigour and excellence, societal impact and engagement, and self-care. This is especially evident in the growing literature by early-career researchers describing the challenges of pursuing a transdisciplinary research career in social-ecological sustainability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 78 publications
(126 reference statements)
2
35
0
Order By: Relevance
“…Acknowledging this reality requires us to understand processes of knowledge co-production as an intrinsically relational practice that necessitates care. As the way in which we pursue our research has “world-making effects” (Puig de la Bellacasa 2017 : 30) and might be materialised in concrete policies, practices and institutions that shape processes towards more (un)sustainable futures, we are required to engage in practices of thinking with care to develop responses to sustainability crises (Sellberg et al 2021 ).…”
Section: A Feminist Ethos Of Care: Puig De La Bellacasa’s Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Acknowledging this reality requires us to understand processes of knowledge co-production as an intrinsically relational practice that necessitates care. As the way in which we pursue our research has “world-making effects” (Puig de la Bellacasa 2017 : 30) and might be materialised in concrete policies, practices and institutions that shape processes towards more (un)sustainable futures, we are required to engage in practices of thinking with care to develop responses to sustainability crises (Sellberg et al 2021 ).…”
Section: A Feminist Ethos Of Care: Puig De La Bellacasa’s Frameworkmentioning
confidence: 99%
“…However, they run the risk of solely placing responsibility on individual researchers to enact self-care and obfuscating structural barriers in academia (Care et al 2021 ; Fischer et al 2012 ). Structural barriers of academic institutions go beyond the reward and evaluation systems of researchers that most often foster individual and high-pace productivity, and include the lack of measures to establish a healthy work-life balance and a caring system for researchers (Sellberg et al 2021 ). While there are some discussions on motherhood and how to foster an inclusive working environment in universities and research centres (Leventon et al 2019 ), less is discussed when researchers (often women) have to take care of their elderly care-givers or family members with chronic diseases or disabilities.…”
Section: Cultivating Caring Academic Culturesmentioning
confidence: 99%
See 1 more Smart Citation
“…Transdisciplinary sustainability researchers often target interdisciplinary research that encourage the ability to speak and move with agility across disciplines and epistemologies while developing their core discipline and becoming grounded in specific methods [71,72]. For example, Sellberg observed that to limit the risk of the research process that involves transdisciplinary approaches becoming more of a consultancy project, a transdisciplinary researcher needs to make sure that the cocreation process has sufficient space for learning, exploration and reflection, [73].…”
Section: Nordic-argentinian Cooperationmentioning
confidence: 99%
“…For instance, protected area rangers can come from or live in the communities they police, which may create tensions with friends, neighbours, and family 18 . In other cases, conservationists can face hard choices when trading-off objectives 19 , which could be compounded by the challenges of interdisciplinary research and practice 20 and ideological con icts with peers (e.g., 21 ). These challenges are not equally experienced within the sector and can vary by job role, geography, race and ethnicity, sexual orientation, religion, gender, and other identities and social relations [22][23][24] .…”
Section: Introductionmentioning
confidence: 99%